Parents' perceptions of their adolescent children's personal values: truth or bias?. Issue 3 (3rd July 2019) - Barni, Daniela; Ranieri, Sonia; Ferrari, Laura; Danioni, Francesca; Rosnati, Rosa
ABSTRACT: Interest in research and theory of the transmission of values between generations has increased markedly in the past few years. Numerous studies have shown that parents' effectiveness in socializing their children may depend on their own perceptions of their children's attributes. Focusing on parents' perceptions of their adolescent children's personal values, this study compared parental perceptions to adolescents' self-reported personal values and examined the relative importance of adolescents' personal values (the 'truth'), parents' socialization values ('ideal-bias'), and parents' personal values ('self-bias') in guiding parental perceptions. In all analyses, gender of both parents and adolescents was taken into account. Participants were 325 family triads (father, mother, and one adolescent child) who completed the Portrait Values Questionnaire. Findings pointed to significant differences between parents' perceptions of their adolescent children's personal values and adolescents' self-reported values, and showed that parents' perceptions are a mix of truth and ideal-bias, which vary according to gender composition of the parent–adolescent dyads.